Magnetic properties and coupled spin-phonon behavior in quasi-one-dimensional screw-chain compound BaMn2 V2 O8 - Pal A.; Anand K.; Yen T.W.; Patra A.; Das A.; Huang S.M.; Blundo E.; Polimeni A.; Yang H.D.; Chatterjee S. (My University, 2025)
Spin-chain compounds are known to exhibit fascinating magnetic properties, which mostly display magnetic ordering at very low temperatures or remain dynamic even at 0 K. In contrast, the present quasi-one-dimensional spin-chain system BaMn2V2O8 exhibits a collinear antiferromagnetic (AFM) long-range ordering at a relatively higher temperature TN∼37K, wherein the nearest-neighbor spins have AFM coupling along the spin chain, i.e., along the c axis. The present study also reveals a short-range magnetic ordering prevailing at considerably elevated temperatures above its TN. Temperature-dependent Raman spectroscopy demonstrates an occurrence of spin-phonon coupling below TN at least for two phonon modes, whereas the study also shows an unusual thermal evolution of the Raman modes above TN, which is apparently associated to the short-range magnetic ordering. Furthermore, extensive ab initio density functional theory calculations accompanied with classical Heisenberg model based theoretical calculations of various exchange interaction parameters (J0-J5) suggest an AFM ground state, which matches well with the experimentally obtained spin structure. © 2023 American Physical Society.